Ordered Hierarchical Mesoporous/Macroporous Carbon: A High-Performance Catalyst for Rechargeable Li-O2 Batteries - Guo, Ziyang; Zhou, Dandan; Dong, XiaoLi; Qiu, Zijie; Wang, Yonggang; Xia, Yongyao (Advanced materials (Weinheim), 2013)
Three‐dimensional ordered mesoporous/macroporous carbon sphere arrays (MMCSAs) are synthesized and then used as a catalyst for Li−O2 batteries. The hierarchical porous structure of the MMCSAs not only facilitates electrolyte immersion and Li+ diffusion but also provides an effective space for O2 diffusion and O2/Li2O2 conversion, and thus efficiently improves the performance of Li–O2 batteries.